NEK5 interacts with LonP1 and its kinase activity is essential for the regulation of mitochondrial functions and mtDNA maintenance - Camila de Castro Ferezin (FEBS Open Bio, 2021)
Little is known about Nima‐related kinase (NEKs), a widely conserved family of kinases that have key roles in cell‐cycle progression. Nevertheless, it is now clear that multiple NEK family members act in networks, not only to regulate specific events of mitosis, but also to regulate metabolic events independently of the cell cycle. NEK5 was shown to act in centrosome disjunction, caspase‐3 regulation, myogenesis, and mitochondrial respiration. Here, we demonstrate that NEK5 interacts with LonP1, an AAA+ mitochondrial protease implicated in protein quality control and mtDNA remodeling, within the mitochondria and it might be involved in the LonP1‐TFAM signaling module. Moreover, we demonstrate that NEK5 kinase activity is required for maintaining mitochondrial mass and functionality and mtDNA integrity after oxidative damage. Taken together, these results show a new role of NEK5 in the regulation of mitochondrial homeostasis and mtDNA maintenance, possibly due to its interaction with key mitochondrial proteins, such as LonP1.